Antagonistic activity of endophytic fungi from Maize plants (Zea mays L.) against Fusarium oxysporum Schltdl. - Aji Oktira Roka; Rofiyanti Dilla (BIO Web of Conferences)
Endophytic fungi were microorganisms that resided within plant tissues without harming their host plants. These fungi acted as biological agents against harmful fungi by utilizing mechanisms like competing for nutrients, parasitism, and antibiosis. This research aimed to isolate and identify the genus groups of endophytic fungi from maize plants (Zea mays L.) and understand the antagonistic mechanisms between endophytic fungi and Fusarium oxysporum Schltdl. Through dual culture tests, the highest inhibitory percentage of endophytic fungi against Fusarium oxysporum Schltdl is determined. in the filtrate and volatile compound tests. Antagonistic activity against pathogenic fungi was determined in vitro through dual culture methods, filtrate culture methods, and volatile compound production. Data obtained from the antagonistic activity of endophytic fungi were analyzed based on the calculation of inhibition percentages. The dual culture method revealed eight isolates effectively restraining the growth of Fusarium oxysporum Schltdl. Among the filtrate culture experiments, isolate B1.1.1 exhibited the most promising outcomes with an inhibition rate of 39.83%. Notably, isolate D2.2.1 displayed the highest inhibition rate of 44.38% in the antagonism test employing the volatile compound production method. Identification was conducted through ITS gene amplification, confirming that isolate D2.2.1 corresponded to Trichoderma harzianum. This research aimed to improve productivity and food security by managing plant diseases, thereby contributing to the achievement of SDG 2 (Zero Hunger).